Pengaruh Kualitas Produk Makanan Dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Di Ruby Restoran Royal Hotel N’ Lounge - Anggraini, Cristian Rizqi; Juhanda (Universitas Muhammadiyah Jember, 2023)
A hotel is a building that provides accommodation, food and drink, where guests who visit do not only aim to stay. Food and beverages are hotel products that provide the second largest input after rooms. Therefore, to remain competitive in the food and beverage sector, both with other hotels and restaurants, it is necessary to increase customer satisfaction with food and beverage products. In this study, we will discuss the influence of food product quality and customer satisfaction on customer loyalty at Ruby Restaurant Royal Hotel N' Lounge. This study aims to determine the variable quality of food products and customer satisfaction have an influence on customer loyalty and to determine the most dominant influence between food quality and customer satisfaction on customer loyalty. Respondents from this study were 100 guests of the royal n lounge hotel and were randomly selected. The research process begins with research instrument testing, interviews and distributing questionnaires to obtain primary and secondary data. The data that has been obtained is tested using multiple linear regression which is processed with SPFF software. The final stage in this research is the preparation of a final report based on the results of data analysis and scientific publications as the output of this research. This study resulted in the conclusion that there is an effect of food product quality on customer loyalty, there is an effect of customer satisfaction on customer loyalty and there is a simultaneous effect of food product quality and customer satisfaction on customer loyalty at Ruby Restaurant Royal Hotel N' Lounge